Experimental modeling of chemical burning of the esophagus using different concentrations of alkali solution - I. Yu. Karpova; P. V. Peretyagin; N. Yu. Orlinskaya; T. E. Potemina; V. V. Parshikov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
The purpose and objectives of the study: is to create an experimental model of a chemical burn of the esophagus with alkali to study the pathological transformation of the tissues of the upper gastrointestinal tract.Materials and methods. On the basis of the Department of Experimental Medicine with a vivarium of the Privolzhsky Research Medical University, the study of a chemical burn of the esophagus was carried out on 15 sexually mature male Wistar rats. The burn was simulated by exposure to caustic soda (NaOH) with a concentration of 20 %, 15 %, 10 % and 5 % in a volume of 1 ml. As part of the morphological study, the experimental material was fixed in 10 % formalin. After fixation, the preparations were sent to a standard histological wiring using an Excelsior ES apparatus (Thermo Scientific). Pouring into paraffin blocks using the “HistoStar” filling station (Thermo Scientific), staining with hematoxylin and eosin. For morphometric processing and creation of a video archive of the obtained material, a Leica 2500 microscope, ×4, ×10, ×20, ×40, objective, ×10 eyepiece based on the morphology department of NIITO PIMU was used.Results. Seeding with a 20 % alkali solution for animals turned out to be incompatible with life, since a day after the injection of the substance, 3 rats died, 2 were in an agonal state. Morphological examination revealed total necrosis (100 %) of the epithelial lining up to the muscle layer and partially in the muscle layer. When burned with a 15 % NaOH solution, the males were in a very serious condition, out of 5 inoculated in 2 cases, a lethal outcome was noted on the 1st day. Histological examination revealed massive necrosis (70 %) of the epithelial lining. The effect of 10 % alkali on the general condition of the animals did not show a pronounced severity of injury. Necrosis was diagnosed on 15 % of the area of the epithelial lining. A burn with 5 % sodium hydroxide solution did not provoke a severity incompatible with life. In this condition, focal necrosis was revealed, occupying about 5 % of the organ area.Conclusion. Seeds with 10 % and 5 % caustic solutions are relevant for further experimental research, since they make it possible to test different methods of diagnostics, treatment and prevention of scarring at different depths and morphological features of damage.